Analysis of Treated Wastewater Produced from Al-Lajoun Wastewater Treatment Plant, Jordan - Waleed Manasreh; Atef S. Alzaydien; Malahmeh .M (E-Journal of Chemistry)
Assessment of treated wastewater produced from Al-Lajoun collection tanks of the wastewater treatment plant in Karak province was carried out in term of physical properties, its major ionic composition, heavy metals and general organic content, for both wastewater influent and effluent. Sampling was done in two periods during (2005-2006) summer season and during winter season to detect the impact of climate on treated wastewater quality. Soil samples were collected from Al-Lajoun valley where the treated wastewater drained, to determine the heavy metal and total organic carbon concentrations at same time. The study showed that the treated wastewater was low in its heavy metals contents during both winter and summer seasons, which was attributed to high pH value enhancing their precipitations. Some of the major ions such as Cl-, Na+, HCO33-, Mg2+ in addition to biological oxygen demand and chemical oxygen demand were higher than the recommended Jordanian guidelines for drained water in valleys. The treated wastewater contained some organic compounds of toxic type such as polycyclic aromatic hydrocarbons. Results showed that the soil was low in its heavy metal contents and total organic carbon with distance from the discharging pond, which attributed to the adsorption of heavy metals, total organic carbon and sedimentation of suspended particulates. From this study it was concluded that the treated wastewater must be used in situ for production of animal fodder and prohibit its contact with the surface and groundwater resources of the area specially Al-Mujeb dam where it is collected.